Size matters! Lying and Mistrust in the Continuous Deception Game - Tobias Beck (ZBW - Leibniz Information Centre for Economics, 2020)
I present a novel experimental design to measure lying and mistrust as continuous variables on an individual level. My experiment is a sender-receiver game framed as an investment game. It features two players: firstly, an advisor with complete information (i.e., the sender) who is incentivized to lie about the true value of an optimal investment and, secondly, an investor with incomplete information (i.e., the receiver) who is incentivized to invest optimally and therefore must rely on the alleged optimum reported by the advisor. Due to its continuous message space, this experiment allows observing more differentiated behavior and therefore enables testing of more sophisticated theoretical predictions. I find that the senders lie by overstating the true value of the optimum to an average extent of about 148%, while the receivers suspect them to do so by only 56%. Moreover, my results indicate that the senders make strategic considerations about their potential to manipulate others when deciding about the sizes of their lies. However, I find that the size of the lie and the size of mistrust do not only matter from a strategic perspective but also have an impact on how people perceive their own behavior. Consistent with previous studies, my findings support the conjecture that lying costs increase with the size of the lie. Beyond that, I provide evidence for some endogenous preference for trust. Both players' behaviors and beliefs are consistent over time. In addition, my classification of both players' strategies is consistent with their self-assessment of their behavior within the experiment.
Keywords: C91; D01; D82; G41; 330; Size of the lie; Size of mistrust; Honesty; Deception Game; Investments; Asymmetric information; Experimental design